Montagnes en bataille. Une géopolitique du refuge depuis la vallée de la Clarée - Pierre Chomette (Revue de Géographie Alpine)
Toward the end of the 20th century, several major development projects that had been proposed in the Briançon area were defeated thanks to collective mobilization efforts. New initiatives now challenge the socio-spatial segregation of exiled people who are trying to cross the border amid the latter’s heavy militarization and in the context of the sensationalist coverage of events by the media. This article examines the discourses produced around these struggles, as well as people’s memories –in particular, that of Émilie Carles (1900–1979). The article considers their impact on how the “mountain” is perceived and hypothesizes that it can play a role in the dynamics of how mountain spaces are essentialized and their inhabitants naturalized. We find that the theme of a “mountain-refuge” is reactivated and enriched by the political work done by local memories. Through a critical geographical approach, this article carries out a political analysis of the figures of the mountain-refuge and links the issues of exile and ecology in order to contribute to thinking on the future of mountain areas.